Higher bacterial DNAemia can affect the impact of a polyphenol-rich dietary pattern on biomarkers of intestinal permeability and cardiovascular risk in older subjects. - Gargari, Giorgio; Taverniti, Valentina; Del Bo', Cristian; Bernardi, Stefano; Hidalgo-Liberona, Nicole; Meroño, Tomás; Andres-Lacueva, Cristina; Kroon, Paul A.; Cherubini, Antonio; Riso, Patrizia; Guglielmetti, Simone (European Journal of Nutrition, 2022)
Purpose: Aging can be characterized by increased systemic low-grade inflammation, altered gut microbiota composition, and increased intestinal permeability (IP). The intake of polyphenol-rich foods is proposed as a promising strategy to positively affect the gut microbiota–immune system–intestinal barrier (IB) axis. In this context, we tested the hypothesis that a PR-dietary intervention would affect the presence of bacterial factors in the bloodstream of older adults. Methods: We collected blood samples within a randomized, controlled, crossover intervention trial in which older volunteers (n = 51) received a polyphenol-enriched and a control diet. We quantified the presence of bacterial DNA in blood by qPCR targeting the 16S rRNA gene (16S; bacterial DNAemia). Blood DNA was taxonomically profiled via 16S sequencing. Results: Higher blood 16S levels were associated with higher BMI and markers of IP, inflammation, and dyslipidemia. PR-intervention did not significantly change bacterial DNAemia in the older population (P = 0.103). Nonetheless, the beneficial changes caused by the polyphenol-enriched diet were greatest in participants with higher bacterial DNAemia, specifically in markers related to IP, inflammation and dyslipidemia, and in fecal bacterial taxa. Finally, we found that the bacterial DNA detected in blood mostly belonged to γ-Proteobacteria, whose abundance significantly decreased after the polyphenol-rich diet in subjects with higher bacterial DNAemia at baseline. Conclusions: This study shows that older subjects with higher bacterial DNAemia experienced a beneficial effect from a polyphenol-rich diet. Bacterial DNAemia may be a further relevant marker for the identification of target populations that could benefit more from a protective dietary treatment. Registration: This trial was retrospectively registered at www.isrctn.org (ISRCTN10214981) on April 28, 2017.